The Implementation Of Blended Learning Method In The Post-Covid-19 Period In Teacher Profession Course At Langlangbuana University - Sri Rohartati (International Conference on Elementary Education, 2023)
This study aims to analyze the use of the blended learning method or the combination of face-to-face learning and online learning in the post-covid-19 pandemic in the Teacher Profession course Langlangbuana University. The university provides the opportunity for 2 courses for each department to hold limited face-to-face lectures (Offline). Offline lectures are accompanied by a faculty operator who will operate IT. During lectures, students can attend limited face-to-face lectures offline and online. Students who meet the requirements can take online lectures directly on campus (face to face) and students who do not meet the requirements can take online lectures. The method used in this research is descriptive qualitative method. The data were obtained from observations and interviews with lecturers and students which were then triangulated. The findings revealed that the synthesizing of knowledge and acquisition of information syntax is maximized during face-to-face meetings and the seeking of information syntax is maximized during online learning. The learning assessment used are assessment of attitudes, knowledge, and skills. Factors supporting the blended learning method include the government, teachers, technology, and parental support. The inhibiting factors for the blended learning method include time, unstable internet connection, lack of motivation to learn, and parents.